LITERATURE REVIEW: POTENSI FRAKSINASI PROPOLIS LEBAH KELULUT SEBAGAI PENELUSURAN AGEN ANTIDIABETES - Sarah, Aulia; Kustiawan, Paula Mariana (Jurnal Buana Farma, 2025)
Diabetes mellitus is a metabolic disorder characterised by hyperglycaemia caused by abnormalities in insulin secretion and insulin action. Indications that arise in people with diabetes include polyuria, hyperphagia and polydipsia. Propolis or bee glue is a product made from plant sources by bees. This study aims to recognise the potential of propolis as an antidiabetic agent in diabetes mellitus. The research method in the literature study by applying journal searches on Google Scholar, PubMed, and ResearchGate databases published in 2010-2024. Based on the results of the article search, 7 suitable journals were identified. These articles consisted of 7 experimental articles. The results showed that propolis can be used as an effective antidiabetic agent to control blood glucose levels, repair damage to the islets of Langerhans, suppress oxidative stress and as an anti-inflammatory. Active compounds contained in kelulut bee propolis such as flavonoids and also other compounds such as phenolics, polyphenols and caffeic acid phenethyl ester (CAPE) compounds. It is also known that propolis treatment can reduce diabetic complications such as nephropathy, retinopathy, leg ulcers, and liver disease. propolis has great potential as a natural antidiabetic drug. The secondary metabolites in propolis, such as flavonoids, terpenoids and saponins, provide various properties including protecting pancreatic β-cells, reducing insulin resistance, and reducing oxidative stress. Fractionation can be one method of exploring the potential of propolis as an antidiabetic.